Oukuriella pesae, a new species of sponge-dwelling chironomid (Insecta: Diptera) from Amazonia, Brazil - Fusari, Lívia Maria; Roque, Fabio O.; Hamada, Neusa (Zootaxa, 2009)
The larva, pupa, male and female of a new Neotropical chironomid species, Oukuriella pesae, are described and illustrated. The larvae were found in freshwater sponge colonies of Oncosclera navicella (Carter, 1881) in Amazonian streams. The morphological characteristics of the larval head and the presence of fine particles in the larval gut contents suggest that the larvae probably feed on the sponge tissue or on other animals that live inside the sponges. Oukuriella Epler, 1986 is currently divided into three species groups, but Oukuriella pesae does not fit any of them.